Cutting Balloon Angioplasty for Severe In-Stent Restenosis after Carotid Artery Stenting: Long-Term Outcomes and Review of Literature - Jeong-Yoon Lee; Min-Surk Kye; Jonguk Kim; Do Yeon Kim; Jun Yup Kim; Sung Hyun Baik; Jihoon Kang; Beom Joon Kim; Hee-Joon Bae; Cheolkyu Jung (Neurointervention, 2024)
Purpose Cutting balloon-percutaneous transluminal angioplasty (CB-PTA) is a feasible treatment option for in-stent restenosis (ISR) after carotid artery stenting (CAS). However, the longterm durability and safety of CB-PTA for ISR after CAS have not been well established. Materials and Methods We retrospectively reviewed medical records of patients with ISR after CAS who had been treated with CB-PTA from 2012 to 2021 in our center. Detailed information of baseline characteristics, periprocedural and long-term outcomes, and follow-up imaging was collected. Results During 2012–2021, a total of 301 patients underwent CAS. Of which, CB-PTA was performed on 20 lesions exhibiting severe ISR in 18 patients following CAS. No patient had any history of receiving carotid endarterectomy or radiation therapy. These lesions were located at the cervical segment of the internal carotid artery (n=16), proximal external carotid artery (n=1), and distal common carotid artery (n=1). The median time interval between initial CAS and detection of ISR was 390 days (interquartile range 324–666 days). The follow-up period ranged from 9 months to 9 years with a median value of 21 months. Four patients (22.2%) were symptomatic. The average of stenotic degree before and after the procedure was 79.2% and 34.7%, respectively. Out of the 18 patients receiving CB-PTA, 16 (88.9%) did not require additional stenting, and 16 (88.9%) did not experience recurrent ISR during the follow-up period. Two patients who experienced recurrent ISR were successfully treated with CB-PTA and additional stenting. No periprocedural complication was observed in any case. Conclusion Regarding favorable periprocedural and long-term outcomes in our single-center experience, CB-PTA was a feasible and safe option for the treatment of severe ISR after CAS.